The Mind depression - Pollard, Sam; Sage, DeWitt (The Mind series, 1988)
Depression is a disease that affects an estimated ten million Americans, roughly eight percent of the U.S. population. This episode follows the lives of a number of people who suffer from depression or manic-depressive illness. The very serious risk of suicide in the chronically depressed person is discussed. Researchers offer their explainations of the origins of depression and try to separate normal mood variations from serious or chronic symptoms.